In the Segment of Social Catering in University - M. A. Belyaeva; А. Yu. Sokolov (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
The article studies views of customers on the vending system in social catering – students and employees of a big economics university. It found out criteria/conditions of vending machine functioning, advantages and disadvantages of the automated system of selling food and drinks. The authors formulated recommendations aimed at upgrading the vending system of servicing in conditions of complicated economic situation, COVID-19 pandemic and restructuring of the catering system. It is reasonable to propose diversification of the product range, new market positions (for instance, snacks for healthy nutrition), search for new market segments / niches and so on.  The authors show the need to improve quality control, especially at the stage of income control while purchasing food and products of extra (non-food) range. They provide interesting information about new functions of vending machines, for example, copying units.